Collaborative governance for lesbian in prison in Indonesia: a literature review - Cahyoko Edi Tando; Mulyani Rahayu (Proceeding International Conference on Religion, Science and Education, 2023)
Lesbian cases in prison in Indonesia that are happening at this time should be of concern to all parties, not only the prison Institutional authorities, but also involving health agencies which are the realm of their authority when infectious diseases occur in prisons. Therefore, a mechanism for inter-agency cooperation or collaborative governance, including involvement with the community, is also needed as an effort to monitor the case. The research method uses a literature review with several reputable journal articles. The purpose of the research will be input to interested parties in prison management, including those who may cooperate with prisons, including health agencies authorities. The results will be in the form of recommendations from several scientific articles which are summarized using certain methods in accordance with the rules of Literature review so that it will facilitate the flow of data submission, the use of year limits in the publication of each scientific article will be considered a novelty in this research so that it will add insight and understanding of lesbian cases in women's prisons in Indonesia.